Unveiling the Power of User-Generated Content for Building Consumer Loyalty in the Indonesian Cosmetics Industry - Meilandini, Salsabila Nadhifah; Hussein, Ananda Sabil; Ismail, Taufiq (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
The Indonesian cosmetics industry is expanding rapidly, intensifying competition among leading brands such as Wardah to sustain customer loyalty. This study contributes to digital marketing and consumer behavior research by examining how user-generated content (UGC) shapes brand trust, brand love, and ultimately consumer loyalty. UGC is theorized to enhance both cognitive trust and emotional attachment, which serve as mechanisms linking digital engagement to long-term loyalty. Using an explanatory quantitative design, data were collected from Wardah consumers in Indonesia through purposive sampling and analyzed with Structural Equation Modeling (SEM). The findings demonstrate that UGC significantly influences brand trust, brand love, and loyalty, while trust and love act as mediators that strengthen the relationship between UGC and loyalty. These results underscore the strategic value of consumer-driven content in fostering durable brand–consumer bonds and provide actionable implications for cosmetics firms to craft customer-centric strategies grounded in emotional engagement and trust.